Mapping of smallholder oil palm plantation and development of a growth model - Okarda, B.; Carolita, I.; Kartika, T.; Komarudin, Heru (IOP Publishing, 2018)
Smallholder plantation accounts for 39% of total oil palm plantation in Indonesia, which is currently estimated at 12 million ha.Limited information on spatial distribution of smallholder oil palm and the growth of plantation pose a great challenge for providing information in scientific based.Therefore, information on smallholder oil palm plantation are necessary and they will give valuable input for policy maker and related stakeholders.This study is aimed to generate smallholder oil palm distribution map using optical satellite data of SPOT 7 and investigate the backscatter values of ALOS PALSAR-2 with height and age of oil palm in mineral soil and peatland.We mapped 46,756 ha of smallholder plantation or about 18% of total oil palm plantation in district of Kotawaringin Barat, Central Kalimantan province and 14% of which is located on peatland area.From the result, height to age mineral soil has a strong relationship with R 2 value 0.80 but weak in peatland with R 2 value 0.31.Relationship between height and backscatter in mineral soil has R 2 value 0.43 for HH and 0.30 for HV and in peatland 0.28 for HH and 0.15.Relationship between age and backscatter in mineral soil has moderately strong correlation with R 2 value 0.55 for HH and 0.37 for HV and in peatland 0.36 for HH and 0.28.In all relationship, independent variables are statistically significant with Significance-F value lower than 0.05.In general, height, age, and backscatter relationship in peatland is lower than in mineral soil.Backscatter value can be useful for studying height and age of smallholder oil palm.Further studies are suggested to involve more potential variables and utilize multi temporal datasets in determining height and age of oil palm trees using backscatter values.